2021
DOI: 10.2147/cmar.s329846
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA HLA Complex Group 11 Knockdown Alleviates Cisplatin Resistance in Gastric Cancer by Targeting the miR-144-3p/UBE2D1 Axis

Abstract: Objective Cisplatin (DDP) treatment is one of the most predominant chemotherapeutic strategies for patients with gastric cancer (GC). LncRNA noncoding RNA HLA complex group 11 (lncRNA HCG11) has been confirmed to promote GC progression. This study attempted to investigate the underlying molecular mechanism of HCG11 in DDP resistance of GC. Methods qRT-PCR was performed to evaluate the expression of HCG11, microRNA-144-3p (miR-144-3p), and ubiquitin-conjugating enzyme E2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…Interestingly, our study showed that SNHG10 upregulated the expression of miR-302b. It has been reported that lncRNAs can regulate the expression of miRNAs through methylation pathways [ 32 ]. For instance, the lncRNA PVT1 downregulated miR-146a by increasing the methylation level of the miR-146a gene to regulate tumor growth in prostate cancer [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, our study showed that SNHG10 upregulated the expression of miR-302b. It has been reported that lncRNAs can regulate the expression of miRNAs through methylation pathways [ 32 ]. For instance, the lncRNA PVT1 downregulated miR-146a by increasing the methylation level of the miR-146a gene to regulate tumor growth in prostate cancer [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Zhou et al demonstrated that higher UBE2D1 expression could drive liver cancer aggravation through inhibition of p53-related ubiquitination [ 36 ]. In addition, Li and his team showed that lncRNA HCG11 could reverse the chemotherapy resistance of stomach cancer via the miR-144-3p/UBE2D1 pathway [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…In view that miRNA was the main effectors of LncRNA, we then examined target miRNAs of LncTUG1 in databases and identi ed miR-144-3p. Studies manifested that miR-144-3p is anomalously expressed in multiple neoplasms, for instance, renal clear cell carcinoma, colorectal cancer, etc [26][27][28][29][30] . Our research displayed that miR-144-3p expression reduced in HCC, and induced the neoplasm progression.…”
Section: Discussionmentioning
confidence: 99%